Who Forms Local Institutions? Levels of Household Participation in India's Joint Forest Management Program - Bhagirath Behera, Stefanie Engel (2006)
Participatory approaches aim at achieving representation of a broad segment of local communities, including poor and marginalized groups in natural resource management. Focusing on the case of Joint Forest Management (JFM) in India, this paper analyzes three levels of participation (attendance of decisive meetings, membership in executive committees, and influence on decisions taken) and their determinants. A conceptual model of the different levels of participation and their linkages is presented and tested through econometric analysis of data from 660 households within 55 JFM communities in Andhra Pradesh. Results indicate that participatory approaches have been somewhat successful in achieving representation of marginalized groups in executive committees and their attendance of meetings. Actual decisionmaking processes continue, however, to be dominated by community elites as well as forest department officials.